2014
DOI: 10.1111/tct.12076
|View full text |Cite
|
Sign up to set email alerts
|

What motivates general practitioners to teach

Abstract: To increase the recruitment and retention of GP teachers, it is recommended that teaching organisations give more recognition to teaching as a clinical professional development activity, place more emphasis on GPs' personal enjoyment, professional responsibility and pride in teaching, and increase engagement with practice owners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 16 publications
6
26
0
Order By: Relevance
“…Many reported being a supervisor made them a better GP, concurring with previous reports highlighting the reciprocal trainee-supervisor learning relationship. 1,3,6,25 In line with other research, 26,27 supervisors experienced tension between competing demands of clinical work and supervision as they found themselves being accountable for their own patients, their registrar and the registrar's patients. Managing unpredictable ad hoc interruptions from their registrar was a particular skill to acquire.…”
Section: Discussionmentioning
confidence: 56%
“…Many reported being a supervisor made them a better GP, concurring with previous reports highlighting the reciprocal trainee-supervisor learning relationship. 1,3,6,25 In line with other research, 26,27 supervisors experienced tension between competing demands of clinical work and supervision as they found themselves being accountable for their own patients, their registrar and the registrar's patients. Managing unpredictable ad hoc interruptions from their registrar was a particular skill to acquire.…”
Section: Discussionmentioning
confidence: 56%
“…Opportunity to learn from and alongside medical students, registrars and junior doctors has also been identified as a motivator for GP participation in teaching [17]. An assessment of a VI model delivered in South Australia suggested that a VI training model was associated with an increase in workplace numbers through the attraction to the region of both experienced and training practitioners [18].…”
Section: Introductionmentioning
confidence: 99%
“…Faculty and learner expectations of teachers Kieran Walsh , BMJ Learning Group , London , UK K iani et al have presented an insightful study into the expectations of medical students regarding their medical teachers. 1 The messages are strikingly clear -students rank teaching and interpersonal skills very highly. Personal and professional skills follow close behind.…”
Section: Letters To the Editorsmentioning
confidence: 99%
“…W e thank Thomson et al . for publishing this insightful Australian study. 1 We were drawn to it as, in the face of recruitment challenges, we conducted a similar survey of general practice teachers (GPTs) in October 2013, investigating key issues informing decisions of GPTs on whether or not to offer medical students placements in general practices.…”
Section: Letters To the Editorsmentioning
confidence: 99%